Positron annihilation in Si and GaAs crystals with an applied magnetic field; Physics Letters A; Vol. 59, iss. 3 - Arefyev (Afef'ev, Arefiev) K. P. Konstantin Petrovich; Karetnikov A. S.; Tsoi A. A.; Vorobiev S. A. (1976, 1976)
The narrow components in angular correlation curves of positron annihilation in Si and GaAs were observed. Hence it follows the formation of positronium-like states in semiconductors. Effects of mechanical and radiation treatment of the samples of Ps-states are discussed.